Effective Entrepreneurial Choice: The Role of Rationality and Non-Rationality in Three Entrepreneurs Success Stories - Chong, Anne Michele, Siang Yoon (2007)
Good entrepreneurship is important for economic growth and productivity in any modern economy. The purpose of this dissertation is to research how good entrepreneurial decisions are made. In theory, optimal or rational decision making means choosing the best alternative in response to the problem. However, in reality, people do not act rationally because they often cannot make rational choices. The reason is that people do not have enough brain power, time or resources to process the complex information available to make the rational choice. These problems lead people such as entrepreneurs to make non-rational choices which have three components. The first is the use of procedures and routines. Secondly, non-rational decision makers are automatic pattern seekers and rely on their intuitions. Thirdly, they use their emotions to guide their decision making. These choices are cheap and quick but are prone to errors and biases.